Delivering on the promise of gene therapy for haemophilia. (3rd June 2020) - Pipe, Steven W.
Abstract: The promise of gene therapy is a single treatment ('one and done') that leads to steady‐state expression of endogenous factor VIII or factor IX sufficient to achieve a functional cure (free of recurrent haemophilic bleeding) if not normalized haemostasis. The elimination of the need for continued prophylaxis, or factor replacement following trauma or prior to surgery would lead to annual cost savings. Such optimized health and well‐being would be reaching a level of health equity that was unimaginable several decades ago. 'Before anything else, preparation is the key to success'—Alexander Graham Bell. This quote from the famous inventor, scientist and engineer highlights that, although we currently stand on the threshold of this achievement, delivering on this promise will require broad‐based multistakeholder preparation (scientists, manufacturers, federal regulators, health technology assessors, persons with haemophilia, national advocacy groups and multidisciplinary healthcare teams) with a focused emphasis on education, approval of safe and effective therapies, removal of barriers to access and excellence in clinical delivery .